2013
DOI: 10.1111/nep.12063
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of N‐terminal pro‐brain natriuretic peptide digit number for screening of cardiac disease in new haemodialysis patients

Abstract: The NT-proBNP concentration just before the first dialysis session is a useful tool for screening for cardiac abnormalities. Considering the wide variation of the NT-proBNP cutoff levels depending on each cardiac abnormality, the digit number could be potentially easier to use for initial risk stratification for cardiac disease in new dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…NT‐proBNP is useful to establish a prognosis in heart failure and to identify asymptomatic or symptomatic left ventricular dysfunction, coronary artery disease and myocardial ischemia. In HD patients, NT‐proBNP was proved to be a screener of asymptomatic cardiac disease, a strong predictor of overall mortality in HD patients . Our finding that MLR being positively associated with NT‐proBNP indicated the MLR might be correlated with cardiac function, which was also consistent with our main finding that MLR served as a predictor of CVD deaths in HD patients.…”
Section: Discussionsupporting
confidence: 90%
“…NT‐proBNP is useful to establish a prognosis in heart failure and to identify asymptomatic or symptomatic left ventricular dysfunction, coronary artery disease and myocardial ischemia. In HD patients, NT‐proBNP was proved to be a screener of asymptomatic cardiac disease, a strong predictor of overall mortality in HD patients . Our finding that MLR being positively associated with NT‐proBNP indicated the MLR might be correlated with cardiac function, which was also consistent with our main finding that MLR served as a predictor of CVD deaths in HD patients.…”
Section: Discussionsupporting
confidence: 90%
“…In another study, the NT-proBNP level with a digit number of 5 or greater was found to be associated with cardiovascular diseases in ESRD patients. An NT-proBNP level of 10000 pg/mL was determined as the best cutoff level for left ventricular systolic dysfunction whereas a level of 6000 pg/mL was the best cutoff level for the diagnosis of coronary artery disease in ESRD patients (29). In our study, there was a statistically significant relationship between an NT-proBNP level >12914 pg/ml and LVH.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 52%
“…Malnutrition and inflammation may affect the NT-proBNP level (29). Therefore, interpretation of the NT-proBNP level is even more challenging in the coexistence of overhydration, malnutrition and inflammation in HD patients (30).…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 99%
“…Although previous studies showed that serum biomarkers of cardiac hypertrophy, BNP 7, 17) and NT-proBNP 9, 18) , are useful in predicting all-cause mortality and CVD events in dialysis populations, no study examined the relationship between CTR and risk for CVD events in patients with CKD. In this study, we confirmed the previous findings regarding NT-proBNP.…”
Section: Discussionmentioning
confidence: 99%